A typical analysis of hybrid covert channel using constructive entropy analytics - Krishnamurthy Koundinya, Anjan; Hebbur Satyanarayana, Gururaja (Institute of Advanced Engineering and Science, 2022)
A covert timing channel is based on modulation of the timing information in the network packets in a secured communication. The delicacy of this channel is primarily viewed as single coherent channel thwart the detection from any third-party entity or network admin. The timing covert channel is strenuous to detect under many scenarios due to the intricate complexity of the channel. The exploration of timing covert channel shed light on intrinsic design aspects which elevate understanding to an advanced level. This will effectively bring out elite literature aspects of the timing covert channel for seamless implementation. Supraliminal channels are innocuous message-based channel introduced as a trapdoor in the communication system either intentional or as vulnerability of the system. A hybrid covert channel is the existence of homogeneous or heterogeneous network covert channel variants either at same instant or at different instant of time. For instance, one of possible hybrid covert channel is the co-existence of timing covert channel in transmission control protocol (TCP) and supraliminal channel in voice over internet protocol (VoIP). This paper introduces this variant of the hybrid covert channel and their significance in network communication. The paper also refers to standard measures-entropy, covertness index to understand hybrid covert channel.